Abstracts of papers presented at Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6-15 August 1970 (SCAR/IUGS, 1970)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

The Last of "The Ten". Antarctic Pioneer Still Lives On (Antarctic, 1970)
Publisher: New Zealand Antarctic Society Place: Christchurch
Keywords: Antarktis; Hugh Blackwall Evans; Southern Cross; biografi; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; overvintring

Antarktistraktaten: en ny type internasjonal organisasjon - Engh, Ulf (Stiftelsen, 1970)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk

De konsultative møter under Antarktistraktaten - Hanevold, Truls (Stiftelsen, 1970)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk

Diatoms: Cleaning and Mounting for Light and Electron Microscopy - Hasle, Grethe R; Fryxell, Greta A (Transactions of the American Microscopical Society, 1970)
Publisher: [American Microscopical Society, Wiley]
Keywords: Sørishavet; Weddellhavet; diatomeer; marinbiologi; oseanografi

Cruise reports. International Weddell Sea Oceanographic Expedition : conducted onboard USCGC GLACIER (WAGB-4) - Kvinge, Thor (University of Bergen, 1970)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; geofysikk; oseanografi

International Weddell Sea oceanographic expedition : position and weather journal USCGC Glacier - Kvinge, Thor (University of Bergen, 1970)
Publication Title: Geophysical Institute. Div. A, Physical Oceanography. Report
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; meteorologi; oseanografi

Antarktis uten ispanser - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; geofysikk; geologi

Ønske om fortsatt Antarktis-innsats - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; politikk

Tolv lands polarforskere til Antarktis-møte i Oslo - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; forskning

Glaciological investigations on Deception Island - Orheim, Olav (Antarctic Journal of the United States, 1970)
Keywords: Antarktis; glasiologi

Energetic significance of absorption of solar radiation in polar homeotherms - Øritsland, Nils Are (Antarctic ecology, 1970)
Keywords: Antarktis; fysiologi; seler; stråling; zoofysiologi

Biology and population dynamics of Antarctic seals - Øritsland, Torger (Antarctic ecology, 1970)
Keywords: Sørishavet; biologi; forskning; marinbiologi; seler; zoologi

Norwegian pelagic sealing reconnaissance in the Scotia Sea, 1964 - Øritsland, Torger (Polar Record, 1970)
Publisher: Cambridge University Press
Keywords: Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Sealing and seal research in the south-west Atlantic pack ice, Sept.-Oct. 1964 - Øritsland, Torger (Antarctic ecology, 1970)
Keywords: MV Polarhav; Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Spillet om hvalen i Antarktis - Overrein, Per; Midgaard, Knut ([Universitetet i Oslo], 1970)
Publication Title: Institutt for statsvitenskap
Keywords: Norge; Sørishavet; historie; hvalfangst; hvalfangstkvoter; internasjonal; pelagisk; politikk; statsvitenskap

The political experiment in Antarctica - Sollie, Finn (Bulletin of the Atomic Scientists, 1970)
General discussion of international cooperation in Antarctica. In special issue Antarctica since the IGY; international laboratory for science and diplomacy.
Publisher: Routledge In special issue Antarctica since the IGY; international laboratory for science and diplomacy. Reprinted in Lewis, Richard S. and Smith, Philip S., eds., Frozen future: a prophetic report from Antarctica, New York, 1973.
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; internasjonal rett; internasjonal samarbeid

Den pelagiske fangst : 1937-1969 - Tønnessen, Johan Nicolay (Norges Hvalfangstforbund, 1970)
Publication Title: Den moderne hvalfangsts historie : opprinnelse og utvikling
Keywords: Norge; Sørishavet; fangst; historikk; husholdning; hvalfangst; hvalfangstkvoten; landbruk; pelagisk

Norwegian Antarctic whaling, 1905–68: an historical appraisal - Tønnessen, Johan Nicolay (Polar Record, 1970)
Publisher: Cambridge University Press
Keywords: Norge; Sørishavet; historikk; hvalfangst; hvalfangstkvoten

The Norwegian Antarctic Expedition 1968-69 - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1968, 1970)
Keywords: Dronning Maud Land; Norsk Antarktisekspedisjon 1968-69; biologi; geologi; glasiologi